Grammatical Alliance in Malay Language: A Study of Linguistic Typology - Soraya, Ratna; Mulyadi (Journal of Language Development and Linguistics, 2024)
This article is entitled Aliansi Gramatikal Na Lingua Melayu: Study of Linguistic Typology. This study of the Malay language's grammatical alliance aims to understand (1) the basic construction of clauses, (2) the construction of complex sentences, (3) the pivotal system, and (4) ultimately the definition of the grammar alliance system. This study uses the theory of language typology as the main theory proposed by Comrie. (1988). These research data are clauses and sentences. Qualitative descriptive. This approach aims to understand the existence of the overlap of different external and internal symptoms of the subject being the subject of the study. Data from the coordinative construction and subordinative construction of the Malay language typologically leads to the finding that in syntax, the Malay languages treat S equally with A, and give different treatment to P (S`=`A`≠ P). The Malay language is a group of languages that works with the S/A pivot system. A system of grammatical alliances such as this suggests that Malay is syntaxically a language of nominative-akusative type. Observing the behavior of S on the intransitive clause with the behaviour of A and P on the transitive clauses of Malay language which indicates that S is equal to A and equally equal with P, then morphologically Malay language has a tendency as a nominative-akusative language.